Evaluation of Fusarium Head Blight and Barley Yellow Dwarf Virus Incidences and Severity Among Winter Wheat Association Mapping Population - Zhu, Daniel; Tidakbi, Lawrence; Wang, Hong; Rupp, Jessica; Jordan, Katherine (My University, 2023)
Fusarium head blight (FHB) and Barley Yellow Dwarf Virus (BYD) are diseases in winter wheat (Triticum aestivum) that caused an estimated $2.7 billion in damage and 0.65 bushels/acre in yield loss in a three-year period, respectively. Disease-resistant lines are the most efficient way to combat disease pressure. Disease resistances are quantitative in nature and many genes have not been well characterized. In addition, several minor effect QTLs identified in wheat make it difficult to design effective markers for resistance to FHB and BYD. Thus, the aim of this study is to identify genetic markers in genomic regions associated with resistance phenotypes. To do this, a panel of 270 different winter wheat lines from across the wheat-growing regions in the United States were scored for disease incidence and severity in the Kansas State University FHB nursery. The causative agent for FHB was introduced via corn spawn and the BYD was presented via natural infection by aphids. These wheat lines were also sequenced using exome capture, providing 450,000 high-quality SNPs for genome-wide association study (GWAS). We observed phenotypic variation in the field, suggesting an association study can be done. There were 30 significant (p<0.00001) SNPs for BYD resistance/susceptibility and 9 significant (p<0.0001) SNPS for FHB resistance/susceptibility. We identified 26 lines representing 10.4% of the total lines carrying the major Fhb1 resistance gene with lower area under the disease progressive curve (AUDPC) compared to the lines with no Fhb1 gene. Our results suggest that high-quality markers for both diseases may be designed. In the future, we hope to test these SNPs by developing KASP assays for these QTLs and validate the SNPs as gene markers in our trial population.
Keywords: Wheat; Fusarium head blight; BYDV; Plant disease; GWAS; USDA NIFA 2019-67032-29071